O lugar e a especificidade da educação na filosofia prática de Kant - Andrade, Renata Cristina Lopes [UNESP]; Carvalho, Alonso Bezerra de [UNESP] (My University, 2013)
We point out the practical philosophy of Kant constituted and sustained, appropriately, of two parts: i) a pure part (not empirical), in which the moral principle is searched and fixed, ii) empirical part, which consists of the verification of the possibility of effectiveness of the supreme principle of morality, at that time, taking into account the condition and characteristics of human nature. The Education, as conceived by Kant, composes one of the parts of his practical philosophy, the empirical one (or the second part of morality), which treats morality applied to humans - the action usually with moral value, in this case, through education. We believe that effective moral education pathway through a possible moral formation (formation and character development) can be better understood when shown and located the unique place that education occupies within the Kantian moral thinking, and when we set its peculiarities. In other words, when we reflect on some issues, such as education, according to Kant, can achieve moral action? Can effect the morality? Or, according to Kant, ethics can be taught? Weigh that in locating the proper place that education occupies in his practical philosophy, we assess these issues more safely. In the present work we will seek exploring the own place and the specifics of Education in Practical Philosophy of Kant, which means, in addition, address the complex action of Kant to develop your practical thinking.

Podemos apontar a filosofia prática de Kant constituída e sustentada, apropriadamente, por duas partes: i) uma parte pura (não empírica), na qual o princípio moral é buscado e fixado; ii) uma parte empírica, que consiste na verificação da possibilidade de efetividade do princípio supremo da moralidade, nesse momento, levando-se em conta a condição e as particularidades da natureza humana. A educação, conforme concebida por Kant, compõe uma das partes de sua filosofia prática, isto é, a parte empírica (ou a segunda parte da moral), a qual tratará da moralidade aplicada ao ser humano – a ação em geral com valor moral, nesse caso, via educação. Pensamos que a efetivação moral via educação, mediante uma possível formação moral (formação e desenvolvimento do caráter) pode ser melhor evidenciada e compreendida quando localizamos o lugar singular que a educação ocupa no interior do pensamento moral kantiano, bem como quando estabelecemos as suas peculiaridades. Noutras palavras, ao refletirmos acerca de algumas questões, tais como: a educação, segundo Kant, pode alcançar a ação moral? Pode efetivar a moralidade? Ou, segundo Kant, a ética pode ser ensinada? Pesamos que, ao localizar o lugar próprio que a educação ocupa em sua filosofia prática, poderemos avaliar tais questões com mais segurança. No presente trabalho buscaremos explorar o lugar próprio e as especificidades da Educação na Filosofia Prática de Kant, o que significa, ademais, abordar a complexa ação de Kant ao desenvolver o seu pensamento prático.
Place and specificity of education in practice philosophy of Kant
Keywords: Kant; Practical Philosophy; Morality; Pedagogy; Education; Kant; Filosofia Prática; Moralidade; Pedagogia; Educação